Kegiatan Sosial Salurkan Ekspresi, Menumbuhkan Harapan di Panti Yatim dan Dhuafa Yauma Pilangsari, Kec. Kedawung, Kab. Cirebon, Jawa Barat - Yani Trihandayani; Ruswati Ruswati; Primadana Primadana; Abdul Azis R; Dio F; Muh. Faisal Ghani; Inesya Azzahra Putri (Compromise Journal Community Proffesional Service Journal, 2025)
Every individual hopes for a better life, but not everyone has the same opportunity to achieve it. Various life challenges, such as economic limitations, lack of access to education, health, and social support, often become barriers for some people. This condition creates social inequality that makes many individuals lose their enthusiasm and motivation in living life. Early childhood dental health is a crucial issue that requires serious attention, considering the high prevalence of dental caries which is influenced by various factors, including inadequate tooth brushing habits and excessive consumption of sweet foods. This Community Service aims to analyze the level of knowledge about dental health, tooth brushing practices in children, and patterns of sweet food consumption on the incidence of dental caries at the Yauma Pilangsari Orphanage and Dhuafa Cirebon. The Community Service method used was an observational analytic with a cross-sectional design, involving 24 early childhood participants. The results of the Community Service revealed that 62.5% of children experienced dental caries, an alarming figure. Of these, 53.1% of children exhibited improper brushing habits, while 54.7% frequently consumed sweet foods. It is important to remember that children's dental health is a shared responsibility between parents, educators, and the community. With a good understanding of the importance of maintaining dental health from an early age, as well as support from various parties, it is hoped that children can grow up with healthy and strong teeth, which will ultimately improve their overall quality of life.